STRATEGI KEPALA MADRASAH DALAM PENGUATAN KARAKTER PESERTA DIDIK - Fakhriyyatul Fuadah; Ainur Rofiq (Pedir Research Institut, 2022)
The principal as a leader, manager, and supervisor, must have stepped into the character education process. The principal as a determinant of the direction of education and policymakers have an important role so that character values are embedded in the school community. Education in essence gives birth to the concept of transferring experience to the students, the activities of transferring experience and its development then occupy a special place in the teaching and learning process. MI Nizhamiyah Rejoagugung Ploso is one of the Islamic school which is chosen as a favorite school of the people in the northern region of the Jombang Brantas River because it is known to have students who have noble character.The focuses of this research are: (1) what is the strategy of the Islamic school principal in strengthening the character of students at MI Nizhamiyah Rejoagung Ploso Jombang? (2) What are the obstacles for the head of the islamic school in strengthening the character of students at MI Nizhamiyah Rejoagung Ploso Jombang? The objectives of this study are: (1) To describe the strategy of the head of the Islamic school in strengthening the character of students at MI Nizhamiyah Rejoagung Ploso Jombang. (2) To describe the constraints of the islamic school principal in strengthening the character of students at MI Nizhamiyah Rejoagung Ploso Jombang. To achieve the above objectives, a descriptive qualitative approach was used by taking the background of MI Nizhamiyah Rejoagung Ploso Jombang with the subject of teachers and other teaching staff. Data were collected by observation, interviews, and documentation. Data analysis was carried out by collecting data, reducing data, presenting data, and drawing conclusions. The validity of the data is done by triangulation, and the use of reference materials. The results of this study indicate that: (1) The strategy used by the islamic school principal in strengthening the character of students is through habituation to religious values, discipline values, and environmental care values. Routine activities and programmed activities are expected to strengthen character values in students and finally monitoring and evaluation, in monitoring the development of character education, principals are assisted by their respective homeroom teachers through a liaison book then the results will be brought to regular meetings to evaluate. (2) the obstacles faced by the principal in strengthening the character of students come from within the students themselves (internally) and from outside the students themselves (externally).